Glycolytic Proteins Interact With Intracellular Melatonin in Saccharomyces cerevisiae - Morcillo-Parra, María Ángeles; Valera, María José; Beltran, Gemma; Mas, Albert; Torija, María-Jesús (Frontiers in Microbiology, 2019)
Melatonin is a bioactive compound that is present in fermented beverages and synthesized by yeast during alcoholic fermentation. Many studies have shown that melatonin interacts with some mammalian proteins, such as sirtuins or orphan receptor family proteins. The aim of this study was to determine the intracellular synthesis profile of melatonin in Saccharomyces cerevisiae and to identify the proteins that may interact with this molecule in yeast cells. Melatonin from fermentation samples was analyzed by liquid chromatography mass spectrometry, and proteins bound to melatonin were immunopurified by melatonin-IgG-Dynabeads. Melatonin was produced intracellularly in the lag phase of yeast growth and was exported to the extracellular media during the stationary phase. During this period, melatonin was bound to six proteins with molecular weights from 55 kDa to 35 kDa. Sequence analysis showed that most proteins shared high levels of homology with glycolytic enzymes. An RNA-binding protein was also identified, the elongation alpha factor, which is related to mitochondria. This study reports for the first time the interaction of melatonin and proteins inside yeast cells. These results highlight the possible role of melatonin as a signal molecule and provide a new perspective for understanding its role in yeast.